Pengaruh Indeks Pembangunan Manusia Dan Pengangguran Terhadap Tingkat Kemiskinan Di Kota Palangka Raya - Try Santi E. Situmorang; Desi Natalia; Lidya A. Simanjorang; Lara Lara; Mika Aulia; Nopreo Dandi; Ucok Ucok; Dicky Perwira Ompusunggu (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
Data registered at the Central Bureau of Statistics (BPS) from 2011 to 2022 were used for this study. The poverty rate and human development index (HDI) are used as independent variables against the dependent variable. To determine how much influence the independent variables have on the Linear Probability Model (LPM) regression coefficient, the data was used with the t-test, F-test, and the coefficient of determination and model fixity by performing the LPM model. Furthermore, the F test included HDI and poverty rate, which were measured through the test. The results showed that the human development index has a negative and insignificant impact on the poverty rate of Palangkaraya City, while unemployment has a positive and significant impact.